Determinant Factors on Audience to Watch TV Station in Indonesia - Widyatama, Rendra; Zsolt, Habil Polereczki (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2023)
The competition in the Indonesian TV broadcasting industry is very intense. To win the race, they must capture the audience’s attention. Unfortunately, not all TV stations can gather information about this due to a lack of human and financial resources. References related to this topic are also scarce. This article examines the factors influencing viewers’ choices of TV stations through a mixed-method approach. In qualitative research through Focus Group Discussions, the researchers concluded that there are 23 factors affecting viewers in choosing TV stations. The findings from the quantitative study were tested through a questionnaire instrument involving 1,102 respondents. Based on statistical tests using regression analysis, the researchers obtained an R Square (R2) value of 0.644, which is statistically significant. Partially, through ANOVA testing, the researchers found that 12 independent variables had t-values greater than the t-table value (1.960) with a significance level of <0.05. These 12 variables, from the most significant to the least significant, are X13, X5, X4, X7, X17, X9, X3, X10, X2, X1, X6, and X19. However, when considering the effective contribution percentage, this study produces a different ranking, leading to different recommendations. Therefore, the use of research findings requires careful analysis. Meanwhile, in the same ANOVA test, the researchers concluded that the other 11 variables, namely X8, X11, X12, X14, X15, X16, X18, X20, X21, X22, and X23, had t-values above 0.05, meaning they are not significant. This research significantly contributes to TV station managers in formulating strategies to attract as many viewers as possible.Keywords: Television broadcast, competition, confirmatory factors analyses, television organising, television engagement ABSTRAKPersaingan siaran TV di Indonesia sangat ketat. Untuk memenangkan perlombaan, mereka harus mampu menarik perhatian penonton. Sayangnya, tidak semua stasiun TV dapat mengumpulkan informasi mengenai hal ini karena kurangnya sumber daya manusia dan keuangan. Referensi terkait topik ini juga jarang. Artikel ini mengkaji faktor yang mempengaruhi pemirsa memilih stasiun TV melalui metode campuran. Pada penelitian kualitatif melalui kelompok diskusi terarah peneliti menyimpulkan terdapat 23 faktor yang mempengaruhi pemirsa dalam memilih stasiun TV. Temuan dalam studi kuantitatif, tersebut diuji dalam penelitian kuantitatif melalui instrumen angket, melibatkan 1.102 responden. Berdasar uji statistik melalui analisis regresi, peneliti mendapatkan nilai R Square (R2) sebesar 0,644 secara signifikan. Secara parsial melalui uji ANOVA, peneliti memperoleh hasil bahwa ada 12 variabel independen yang memiliki nilai t lebih besar dari t tabel (1,960) dengan nilai signifikansi < 0,05. Secara berurutan, 12 variabel tersebut yang memiliki nilai signifikani besar sampai nilai signifikansi kecil yaitu variabel X13, X5, X4, X7, X17, X9, X3, X10, X2, X1, X6, and X19. Namun bila menggunakan besarnya prosentase kontribusi efektif, penelitian ini menghasilkan urutan yang berbeda sehingga menghasilkan rekomendasi yang berbeda pula. Oleh karena itu, penggunan hasil penelitian memerlukan analisis yang hati-hati. Sementara itu, dalam uji Anova yang sama, peneliti menyimpulkan bahwa 11 variabel lainnya yaitu X8, X11, X12, X14, X15, X16, X18, X20, X21, X22, and X23 memiliki nilai t di atas 0.05, yang berarti tidak signifikan. Penelitian ini memberi kontribusi signifikan bagi para pengelola stasiun TV dalam menyusun strategi mendapatkan penonton sebanyak-banyaknya.Kata Kunci: Siaran televisi, persaingan, konfirmatori faktor analisis, pengorganisasian televisi, keterlibatan televisi